Interaksi Tropik Jenis Serangga di atas Permukaan Tanah (Yellow Trap) dan pada Permukaan Tanah (Pitfall Trap) pada Tanaman Terung Belanda (Solanum betaceum Cav.) di Lapangan - Antji Aryoudi; Mukhtar Iskandar Pinem; Marheni Marheni (Universitas Sumatera Utara, 2015)
Tropic interaction of insect on soil surface and above soil surface on tamarillo (Solanum betaceum Cav.) in the field. The aim of the research were to knew interaction of insect on soil surface and above soil surface on tamarillo in the field and determined kinds of natural enemies and important pests. The research was conducted at Marubun Village Purba Subdistrict Simalungun Regency and Pest Laboratory Faculty of Agriculture University of Sumatera Utara Medan from November 2014 to January 2015. The traps used. were yellow trap and pitfal trap. The result showed that there were 1.544 insects caught in yellow trap (10 ordos and 35 families) and 187 insects caught in pitfall trap 8 ordos and 18 families. The highest relative density of insects in yellow trap was 57.44% and the lowest valve was 0.13%. Where as, the highest relative density of pitfall trap was 39.57% and the lowest valve was 0.53%. Biodiversity a index of Shanon-Weiner (H’) of yellow trap was 1.76 (medium) and the valve of biodiversity index of pitfall trap was 1.85 (medium).Keywords : interaction, pest, Solanum betaceum, trap